A Simple in situ Assay to Assess Plant-Associative Bacterial Nitrogenase Activity - Haskett, Timothy L.; Knights, Hayley E.; Jorrin, Beatriz; Mendes, Marta D.; Poole, Philip S. (Frontiers in Microbiology, 2021)
Assessment of plant-associative bacterial nitrogen (N) fixation is crucial for selection and development of elite diazotrophic inoculants that could be used to supply cereal crops with nitrogen in a sustainable manner. Although diazotrophic bacteria possess diverse oxygen tolerance mechanisms, most require a sub 21% oxygen environment to achieve optimal stability and function of the N-fixing catalyst nitrogenase. Consequently, assessment of N fixation is routinely carried out on “free-living” bacteria grown in the absence of a host plant and such experiments may not accurately divulge activity in the rhizosphere where the availability and forms of nutrients such as carbon and N, which are key regulators of N fixation, may vary widely. Here, we present a modified in situ acetylene reduction assay, utilizing the model cereal barley as a host to comparatively assess nitrogenase activity in diazotrophic bacteria. The assay is rapid, highly reproducible, applicable to a broad range of diazotrophs, and can be performed with simple equipment commonly found in most laboratories that investigate plant-microbe interactions. Thus, the assay could serve as a first point of order for high-throughput identification of elite plant-associative diazotrophs.